The growth and development of Cape Town - Margaret Marshall (Department of Historical Studies, 2024)
The study of Cape Town is one of particular interest because the growth of the town has been so intimately dependent upon its situation It has been stated that Cape own occupies the most central position in the-world, for it· is nearer to more large ·sea-ports than any other city. Africa south of the Equator-forms a great promontory occupying a central position in relation to the great land masses of Europe, Asia the Americas, and-Australia.